I am dividing (36t^6 -27t^5-9t^2) divided by (-9t^2) I divided the terms together and I got -4t^4 + 3t^3 +1 how would you do yours?
I am dividing (36t^6 -27t^5-9t^2) divided by (-9t^2) I divided the terms together and I got -4t^4 + 3t^3 +1 how would you do yours?
1. (a + 2) (a+2) 2. 12a^3b^2 + 4a^4b^5 + 16ab^2 divided by 4ab^2
1.Evaluate 6s^0 when S = -12 2.simplify (a^5b)^7 (a^8b^5) 3. simplify with no negatives 12y^-2 / 4y^-8 4. use radical notation to rewrite the expression then simplify 36...
Express using positive exponents. Then if possible simplify. 5a^-7 b^4 Odd and even Nth root 4 (7b)^4
What is the solution of 1. 4y=x+4 x=y+2 2. 2x-y=4 4x-2y=4 Solve using the substitute method 3. 7x+8y=-25 x=-1-2y 4. 9x-3y=6 3x-2=y...